PENGARUH PROFESIONALISME AUDITOR, PENGALAMAN AUDITOR, PENGETAHUAN AUDITOR MENDETEKSI KEKELIRUAN DAN PROFESSIONAL ETHICS TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS DALAM AUDIT LAPORAN KEUANGAN (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK (KAP) KOTA MEDAN) - Novera, Delasuci; Ridwan, Muhammad; Ginting, Avissa Reda Putri; Purba, Doli Efredi (EDUTECH CONSULTANT, 2019)
This study aims to examine and provide empirical regarding the effect of the auditors professionalism, auditors experience, auditors knowledge to detect errors, and professional ethics on the materiality level of judgment in an audit of financial statements at 8 Accountant Public Firm in Medan. This study used purposive sampling method. The data were collected through questions survey methods. The results of the study indicate that partially auditor professionalism, auditors experience, and professional ethics had a positive effect and significant on the materiality level of judgment in an audit of financial statements. While auditors knowledge to detect errors had a negative effect and significant on the materiality level of judgment in an audit of financial statement.